2004
DOI: 10.1093/hmg/ddi010
|View full text |Cite
|
Sign up to set email alerts
|

Digenic inheritance of deafness caused by mutations in genes encoding cadherin 23 and protocadherin 15 in mice and humans

Abstract: Mutations in genes coding for cadherin 23 and protocadherin 15 cause deafness in both mice and humans. Here, we provide evidence that mutations at these two cadherin loci can interact to cause hearing loss in digenic heterozygotes of both species. Using a classical genetic approach, we generated mice that were heterozygous for both Cdh23 and Pcdh15 mutations on a uniform C57BL/6J background. Significant levels of hearing loss were detected in these mice when compared to age-matched single heterozygous animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 38 publications
(62 reference statements)
5
92
1
1
Order By: Relevance
“…Mice of the C57BL/6J (B6), DBA/2J (D2), and other strains exhibit genetic age-related hearing loss (for reviews see Erway et al, 1993Erway et al, , 2001Johnson et al, 1997Johnson et al, , 2000Li and Borg, 1991;Zheng et al, 2005). A series of studies has shown this to be ameliorated by treatment with an augmented acoustic environment (AAE) consisting of 12-hour-nightly exposure to noise bursts of 70 dB SPL (re: 20μPa).…”
Section: Introductionmentioning
confidence: 99%
“…Mice of the C57BL/6J (B6), DBA/2J (D2), and other strains exhibit genetic age-related hearing loss (for reviews see Erway et al, 1993Erway et al, , 2001Johnson et al, 1997Johnson et al, , 2000Li and Borg, 1991;Zheng et al, 2005). A series of studies has shown this to be ameliorated by treatment with an augmented acoustic environment (AAE) consisting of 12-hour-nightly exposure to noise bursts of 70 dB SPL (re: 20μPa).…”
Section: Introductionmentioning
confidence: 99%
“…Cadherin and protocadherin mutations are reported to be involved in noise-induced hearing loss [13][14][16][17]44]. The altered expression profile of cadherins and protocadherins in different regions of the brain after repeated blast exposures may impair central auditory processing.…”
Section: Discussionmentioning
confidence: 99%
“…A number of genes and their protein products have been reported to be involved in both age-and noise-related hearing loss [10][11][12][13][14][15]. Cadherin and protocadherin mutations were linked to digenic inheritance of deafness and have specific functional roles in noise-induced hearing loss [13][14][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another mouse model called circling, the mapped locus also includes the Tmie gene [20,21], and the circling mouse also exhibited hair cell axonal and spiral ganglion degeneration [22]. There is a similar pattern of histologic features in Cdh23+/Pcdh15+ and Ush1C +/+ mice [23,24]; additionally, the CDH23, PCDH15, and USH1C proteins have been identified as stereocilia bundling proteins. However, it is difficult to surmise whether the hair cell and/or spiral ganglion loss in the Tmie mouse mutants were due to primary stereocilia defects or to secondary responses to another type of inner ear malfunction.…”
Section: Discussionmentioning
confidence: 99%